2019
DOI: 10.1016/j.heliyon.2019.e02047
|View full text |Cite
|
Sign up to set email alerts
|

Cell cytotoxity and anti-glycation activity of taxifolin-rich extract from Japanese larch, Larix kaempferi

Abstract: The larches, the Larix genus of plants are known as a natural source of taxifolin (dihydroquercetin), and extracts of its taxifolin rich xylem are used in dietary supplements to maintain health. In the present study, to assess biological activities of a methanol extract of the Japanese larch, Larix kaempferi (LK-ME), the effects of LK-ME on cell viability, inflammatory cytokine expression, and glycation were investigated. The effects of taxifolin which is known to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
(26 reference statements)
2
13
0
Order By: Relevance
“…These lower induction activities of quercetin and luteolin on the expressions of LXRβ and ABCG1 mRNAs are thought to be involved in cell cytotoxicity. Our previous study demonstrated that cell cytotoxicity of taxifolin is significantly lower than that of quercetin and luteolin in undifferentiated (monocyte like) THP-1 cells [ 16 ]. As shown in Figure 6 , taxifolin cytotoxicity is also weaker in quercetin and luteolin in macrophage differentiated THP-1 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These lower induction activities of quercetin and luteolin on the expressions of LXRβ and ABCG1 mRNAs are thought to be involved in cell cytotoxicity. Our previous study demonstrated that cell cytotoxicity of taxifolin is significantly lower than that of quercetin and luteolin in undifferentiated (monocyte like) THP-1 cells [ 16 ]. As shown in Figure 6 , taxifolin cytotoxicity is also weaker in quercetin and luteolin in macrophage differentiated THP-1 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have demonstrated that the L. kaempferi methanol extract (LK-ME) exhibits anti-glycation activity [ 16 ]. High performance liquid chromatography (HPLC) analysis has indicated that taxifolin is the main compound in LK-ME, and most of the flavonoids contained in LK-ME are assumed to be taxifolin.…”
Section: Introductionmentioning
confidence: 99%
“…nigra bark [ 120 ] with a maximum extraction recovery of 34%. Taxifolin was detected as the major compound in other needle leaved trees such as the Japanese larch, Larix kaempferi [ 175 ]. Its main bioactivities are antioxidant, anticancer, and anti-inflammatory [ 148 , 167 ].…”
Section: Polyphenols As Extracted Biocompoundsmentioning
confidence: 99%
“…The two extracts were then monitored by the bioassay (BSA-Glucose) method and the chromatography pattern was also observed. In the BSA-Glucose method, the glycation inhibition process can be seen from the formation of fluorescent glycated protein ( Muramatsu et al., 2019 ). This bioassay-guided fractionation method has been previously applied to detect the presence of active fractions from T. diversifolia (Hemsley) A.…”
Section: Discussionmentioning
confidence: 99%